Educating healthcare providers in geriatric oncology – A call to accelerate progress through identifying the gaps in knowledge. Issue 6 (July 2020) - Hsu, Tina; Soto-Perez-de-Celis, Enrique; Burhenn, Peggy S.; Korc-Grodzicki, Beatriz; Wildes, Tanya M.; Kanesvaran, Ravindran; Maggiore, Ronald J.
Abstract: The majority of patients with cancer are over the age of 65. This patient population often has unique care needs. Thus, clinicians require additional competencies and skills to care for this population. Most clinicians, however, receive little to no training in geriatrics. There has been increasing recognition of the importance of learning about geriatric oncology. However, teaching of geriatric oncology principles is not standard or widespread. Here we highlight educational work and scholarship accomplished thus far in the field of geriatric oncology and identify gaps in knowledge that need to be addressed in order to help accelerate the development, implementation, integration, and dissemination of geriatric oncology curricula. These, in turn, will hopefully help improve the knowledge and skills of clinicians caring for older adults with cancer globally.